Apomorphine Targets the Pleiotropic Bacterial Regulator Hfq - Florian Turbant; David Partouche; Omar El Hamoui; Sylvain Trépout; Théa Legoubey; Frank Wien; Véronique Arluison (MDPI AG, 2021)
Hfq is a bacterial regulator with key roles in gene expression. The protein notably regulates translation efficiency and RNA decay in Gram-negative bacteria, thanks to its binding to small regulatory noncoding RNAs. This property is of primary importance for bacterial adaptation and survival in hosts. Small RNAs and Hfq are, for instance, involved in the response to antibiotics. Previous work has shown that the E. coli Hfq C-terminal region (Hfq-CTR) self-assembles into an amyloid structure. It was also demonstrated that the green tea compound EpiGallo Catechin Gallate (EGCG) binds to Hfq-CTR amyloid fibrils and remodels them into nonamyloid structures. Thus, compounds that target the amyloid region of Hfq may be used as antibacterial agents. Here, we show that another compound that inhibits amyloid formation, apomorphine, may also serve as a new antibacterial. Our results provide an alternative in order to repurpose apomorphine, commonly used in the treatment of Parkinson's disease, as an antibiotic to block bacterial adaptation to treat infections.